Weil der Mensch ein Mensch ist . Because a Man is Human - Finsterwalder, Frauke; Hilpert, Stephan (HFF Münich ; Janker, Tina, 2007)
Verzio FF submission Summer holidays in a self-run youth camp. The children democratically vote in their own parliament which gives them the possibility of determining the power structure of the camp. Eleven-year-old Nils gets elected as a representative but soon others get interested in his power and position. When the children overthrow Nils, his political career comes to a sudden end which marks the beginning of his social decline as well.